Iran: Political Economy of an Islamic State (American Journal of Islam and Society, 1985)
INTRODUCTIONPolitical and economic developments in the post revolutionary Iranpresent a special dilemma to outside observers in general and to socialscientists in particular as many developments do not seem to fit theusualpolitical and economic categories with which the social scientists arenormally familiar. As a result, most analysts of contemporary Iran,approaching the reality from the rigidly preconceived conceptual lenses,tend to grossly distort the actual picture. The contemporary situation inIran is usually portrayed as one of utter chaos and turmoil with little orno hope for any progress in the future. It is seen as ruled by “emptyheadkid”,“conservative”, “brutal,” and “incompetent” mullahs who arebent upon destroying any signs of progress and civilization. Eventhe moderate analysts who seem to be less preoccupied with their biasesand more cognizant of the new realities, appear to dismiss any long-termconsequences of the current changes taking place in contemporary Iran.My major objective in the following pages is to develop an alternativeimage of the same reality. I argue here that slowly and gradually, a newpolitical and economic order is emerging in Iran, whose broad objectivesand outlines are clear. A major distinguishing characteristic of thisorder is its public welfarist orientation with special attention to thelower-middle and lower classes. And this order has the potential of sofundamentally transforming the political scene in Iran in the long runwhere the old issues and the old actors are most likely to be irrelevant tothe new type of politics. Once successful, the political implications of thisorder will have a much wider effect on the Muslim world than commonlyassumed.This paper has four sections. The first section deals with the ideology ofthe Islamic republic. Examining the ideas of the leading revolutionarythinkers, we shall try to establish a criteria against which the regime’spolitical and economic performance is to be assessed. The second sectionof the paper describes the nature of key political and economicinstitutions established in the aftermath of the revolution and their modeof functioning. The third part of the paper is concerned with theeconomic performance of the regime over the past five years. We shallassess its performance in two ways: (a) in light of the criteria establishedin the first part of the paper and (b) a brief comparison of the IslamicRepublic’s five year performance with the prerevolutionary Iran’s lastfive-year plan (1973-1978). The final section of the paper summarizes themajor conclusions of this study and also attempts to project a likelyfuture scenario ...